MECHANISMS IN ENDOCRINOLOGY: Pioneer transcription factors in pituitary development and tumorigenesis. Issue 1 (January 2021) - Harris, Juliette; Gouhier, Arthur; Drouin, Jacques
Abstract : Pioneer transcription factors have key roles in development as master regulators of cell fate specification. Only a small fraction of all transcription factors have the pioneer ability that confers access to target genomic DNA sites embedded in so-called 'closed' heterochromatin. This ability to seek and bind target sites within the silenced portion of the epigenome is the basis for their role in changing cell fate. Upon binding heterochromatin sites, pioneer factors trigger remodeling of chromatin from a repressed into an active organization. This action is typically exerted at enhancer regulatory sequences, thus allowing activation of new gene subsets. During pituitary development, the only pioneer with a well-documented role is Pax7 that specifies the intermediate lobe melanotrope cell fate. In this review, a particular focus is placed on this Pax7 function but its properties are also considered within the general context of pioneer factor action. Given their potent activity to reprogram gene expression, it is not surprising that many pioneers are associated with tumor development. Overexpression or chromosomal translocations leading to the production of chimeric pioneers have been implicated in different cancers. We review here the current knowledge on the mechanism of pioneer factor action.